Best Answer

xy + y = z

xy = z - y

(xy)/y = (z - y)/y

x = (z - y)/y

Q: If xy plus y equals z then x equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

It equals y+1

4

y=f(x)= x(2x+y)=7 f(x)=2x^2 +xy -7 = 0 y=2x^2 +xy -7 y-xy -7 + 2x^2 = 0 y(1-x)=2x^2-7 y=(2x^2-7) / (1-x) Excuse the working. Y equals 2 X squared minus 7 all divided by 1-X

0

Just plug in the values for x and y. 4(-1) - 2(5) + (-1)(5) = -19

Related questions

x+xy=8 xy=-x+8 y=-1+8/x

xy = x ÷x y = 1

It equals y+1

x = 6y over (y-6)

x and y are being combined using a binary operation called "plus" and the result is xy.

xy + x + y + 1 = (x + 1)(y + 1).

4

between X and Y

Yes

y=(x+2)/(x+10) xy+10y=x+2 xy-x=2-10y x(y-1)=2-10y x=(2-10y)/(y-1)

xy + z = 9Subtract 'z' from each side:xy = 9 - zDivide each side by 'x':y = (9 - z) / x

(x-y) + (xy - 1) = (x - 1)(y + 1)